Pengaruh Harga, Kualitas Pelayanan, dan Lokasi terhadap Minat Beli Konsumen pada Rumah Makan Mie Endess Arosbaya - Uswatun Hasanah; Octaviana Arisinta; Yusrianto Sholeh (J-MAS (Jurnal Manajemen dan Sains), 2022)
Indonesia has a culinary diversity that stretches from west to east Indonesia and is still embedded in the social life of the local community. Each region has its own unique food because each culture is different from one another. For example, Madurese cuisine is synonymous with spicy salty taste. The development of the Food House business in Bangkalan is progressing very quickly. One example in Bangkalan is Mie whip, Mie endes, and so on. Many things are taken into consideration by consumers to arrive at a decision to choose a particular restaurant or company. The restaurant management must try to meet the criteria that are considered by consumers, both in terms of service quality, price and location so that they can easily attract consumer buying interest. One of them at the Endess Mie Restaurant is a noodle restaurant that is currently popular among young people. Based on the background that arises above, it makes researchers interested in conducting research on "The Effect of Price, Quality and Location on Consumer Interest." This research uses Mie Endes Arosbaya as the object of research. The population in this study was the end of the Arosbaya noodle restaurant and the sample taken was 60 people with questionnaire data as an instrument. The method in this research is quantitative research. This type of research uses associative research. associative research is a type of research that aims to determine the effect of two or more variables. The results showed that price partially had a significant positive effect on consumer buying interest at Arosbaya Endess noodle restaurant, location partially had a significant positive effect on consumer buying interest at Arosbaya Endess noodle restaurant, while service quality partially had no effect on consumer buying interest in Arosbaya Endess noodle restaurant, and simultaneously price, service quality and location have a significant positive effect on consumer buying interest at Arosbaya Endess noodle restaurant.